Effectiveness of lifestyle modification intervention on cardiometabolic risk profile among obese adults - Shahadan, Siti Zuhaidah; Daud, Azlina; Md Isa, Muhammad Lokman; Ibrahim, Muhammad; Draman, Samsul (2016)
Obesity is an independent risk factor for dyslipidaemia. It is expected that lipid profile is improved following weight loss. In Malaysia, lifestyle modification intervention (LMI) has been a treatment modality for obesity since decades ago. However, the evidence of it’s effectiveness on promoting weight loss thus improving lipid profile among obese adults is highly fragmented. This study attempts to determine the effectiveness of LMI on weight status and lipid profile among Malay obese adults in Kuantan. A total of 123 Malay obese class I and II adults aged between 19 to 60 years olds are expected to be randomized to receive either standard care or LMI for 6 months. The intervention group will be followed-up on monthly basis to receive health education consisting of dietary modification, increased physical activity and behavioural modification. On the other hand, the control group will receive a basic health education about obesity and weight management. It is hypothesized that the introduction of LMI will result in significant difference in the weight status and lipid profile of obese adults in intervention group. The findings of this study will provide an evidence of a population-based intervention in the effort of preventing dyslipidaemia among Malay obese class I and II adults.